Patient Safety Culture from the Viewpoint of Nurses: A Cross-Sectional Study in 2016 - Seyed Ali Majidi; Shiva Alizadeh; Sobhaneh kouchakzadeh Talami; Hamideh Safarmohammadi; Ehsan Kazemnezhad Leily; Monika Motagi; Mehdi Barzegar (Journal of Research Development in Nursing and Midwifery, 2019)
Background: Patient safety is one of the main components of the health care services quality that implies avoidance of any harm or damage to the patient during the delivery of health care. The purpose of this study was to determine the patient safety culture from the view point of nurses in the hospitals of Guilan province in 2016. Methods: This cross-sectional study was done on 400 nurses from the nurse community in Guilan province, Iran in 2016. The sampling was performed as the two-stage cluster sampling method. Data were collected using a modified questionnaire based on the Hospital Survey on Patient Safety Culture (HSOPSC). Data were presented with descriptive statistics analysis using in SPSS-14. The significant level was considered less than 0.05. Results: Most of the nurses were female (89%), with a mean age of 34.28±6.86 years. The most response to the items was related to “Please give your work area/unit in this hospital an overall grade on patient safety” that was the acceptable option (47.5%). The mean score of the patient safety was 3.28 ±0.86. Conclusions: The results showed two dimensions including staffing and teamwork within units. Feedback and communication about errors were the most important dimensions of the patient safety culture. Accordingly, it should be noted that paying more attention to the patient safety culture can lead to improve hospital condition levels.